ANALISIS STRATEGI PEMASARAN DAN PENGEMBANGAN PRODUK HIDROPONIK UNTUK MENINGKATKAN DAYA SAING EKONOMI (STUDI KASUS: PERKEBUNAN VALEFARM HIDROPONIK SOLO) - Aditya Ari Prasetya; Yuni Prihadi Utomo (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
This study aims to analyze the marketing strategy and hydroponic product development implemented by Valefarm Hidroponik Solo plantation, with a focus on active participation between researchers and Valefarm through the Participatory Research approach. This method is designed to involve actors involved in every stage of the research, ensuring the sustainability and relevance of the research findings. The study used interviews, focus groups, and participatory sessions to gain an in-depth understanding of the perceptions, knowledge, and experiences that have been implemented by Valefarm regarding marketing strategies and hydroponic product development. The analysis was carried out collaboratively, involving actors involved in the research in interpreting the results and formulating recommendations. The results of the study show that through the Participatory Research approach, Valefarm has succeeded in integrating diverse thoughts and views from researchers, creating a more diverse and relevant marketing strategy. Active participation also facilitates a two-way exchange of knowledge between researchers and Valefarm, increasing a shared understanding of the challenges and opportunities in the hydroponic industry. This study provides in-depth insight into the successful implementation of marketing strategies and hydroponic product development through the active participation of researchers. The findings of this study not only support local economic growth through more contextual marketing strategies but also provide a foundation for sustainable product development that is responsive to market needs. The Participatory Research approach has proven to be an effective tool in understanding and improving economic competitiveness in the context of hydroponic farming.